Islam, Budaya Lokal dan Strategi Komunikasi Politik Digital - Fanyra, Jihan; Ananta, Fahmil (Prodi KPI FDPM IPMAFA Bekerjasama dengan Mafa Press IPMAFA Pati, 2025)
In the digital era, the interaction between Islamic values, Indonesian cultural diversity and social media-based political communication strategies form a new pattern in the dissemination of political messages that not only affect public perception but also the dynamics of democracy and social life of the community. This article aims to examine how Islamic values and local culture are integrated in digital political communication strategies in Indonesia. This study uses a library research approach by relying on literature sources in the form of journals, books, and relevant documents. The discussion fokused on the construction of political messages that utilize local symbols, the transformation of political culture in the digital era, and ethical challenges in Islamic-based political communication. The results of the study show that local culture and Islamic values are often used for electoral purposes through digital media. While effective in building emotional closeness with the public, this practice often ignores Islamic communication ethics that emphasize honesty, prudence, and fairness. These findings highlight the importance of formulating political communication strategies that are not only culturally contextual, but also ethical in value.